Influence of surface reflectivity on radiation in the Antarctic environment - Smolskaia, I.; Wuttke, S.; Seckmeyer, G.; Michael, K.; Slusser, James R.; Schäfer, Klaus; Comerón, Adolfo (Bellingham Wash. : SPIE, 2006)
We demonstrate the importance of surface reflectivity for the radiation field in polar regions by a combination of measurements and radiative transfer calculations. Results from measurements of spectral albedo, radiance and irradiance from 280 to 1050 nm at German Neumayer Station in Antarctica in summer 2003/2004 as well as measurements of UV irradiance during summer 1997/1998 at Australian Davis Station, Antarctica are presented. The impact of surface albedo inhomogeneity is investigated by 3-D Monte Carlo modelling. We found that high surface reflectivity in the ultraviolet and visible parts of the spectrum due to the snow covered surface in Antarctica modifies the radiation field considerably compared to mid-latitudes. A change of the spectral reflectivity, which happens as a consequence of climate change will have a large impact in the radiation properties in polar regions and vice versa.